THE SIZE OF EXTERNAL URETHRAL MEATUS ON MAXIMUM STRETCH IN WEST JAVA PEDIATRIC MALE: IS THERE ANY CORRELATION WITH AGE? - Yudawan, Herman; Sibarani, Jupiter (Indonesian Urological Association, 2020)
Objective: To determine the average size of external urethral meatus in children in West Java, and to find out whether there was a correlation between the size of external urethral meatus and age of boys in West Java. Material & Methods: This research was an analytical with prospective study design. Our research subjects consist of children hospitalized between November 2017-November 2018 at Hasan Sadikin General Hospital, Bandung. Measurement is done by measuring the diameter of the external urethra using meatal calibrator, recorded as meatus size on a French scale. Inclusion criteria in this study were all pediatric patients aged 0-12 years who consented to be involved in the study. The exclusion criteria were patients who had urethral diseases such as hypospadias, epispadias, strictures, and history of instrumentation and interventional procedures on the urethra. After data collection, data were analyzed using SPSS 18. Results: We included 187 patients in our study, with the youngest being 1 month old and the oldest being 12 years. We documented the mean external urethra meatal measurement and grouped the subjects into 4 age groups. The average size of the external urethral meatus in the infant age group (0-12 months) was 5.82 Fr, the toddler age group (1-3 years) it was 6.34 Fr, in the preschool age group (3-6 years) it was 8.51 Fr, and in the primary school age group (6-12 years) it was 12.90 Fr. Based on the results of measurements, there is a correlation between age and external urethral meatal size (p=0,000). The older the child, the greater the size of the external urethral meatus obtained. Conclusion: The size of the external urethral meatus maximum stretch in boys in West Java increases with age. The results of this study are expected to be used as a reference of normal anatomical size, particularly the external urethral meatal size in boys in West Java.